Overall survival nomogram for patients with spinal bone metastases (SBM). (May 2021) - Osong, Biche; Sanli, Ilknur; Willems, Paul C.; Wee, Leonard; Dekker, Andre; Lee, Seok Ho; van Soest, Johan
Highlights: Demographic features are essential for a more personalize survival prediction of spinal bone metastasis (SBM). Women have a relatively better survival chance than men before 75 years, while men have better survival after this age. SBM survival is not dependent on the number of spinal metastases.